Organics Removal in the Treatment of Batik Wastewater using Bench-Scale Sequencing Batch Reactor (SBR) System - Wong, Dai Le (Universiti Teknologi PETRONAS, 2020)
Batik has been one of oldest cottage textile industries in Malaysia. Batik Industries makes a big contribution to the economic growth due to high demands locally and from abroad. However, this industry produces wastewater which contributes to water pollution since it utilizes a lot of chemicals which contains high pH value, chemical oxygen demand (COD), total suspended solids (TSS), intense colour, and heavy metals. Batik factory in Chemor has been one of them which does not have a proper treatment method for treating batik wastewater as only a small amount of batik wastewater has been produced. This study focused heavily on determining feasibility of utilising an aerobic sequencing batch reactor (SBR) to treat batik wastewater and evaluating the performance of organic removal in a bench-scale SBR.